PELAKSAAN PEMBLOKIRAN REKENING BANK OLEH PERBANKAN KAITANNYA DENGAN RAHASIA BANK DALAM PRAKTEK - Masniah Masniah (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTIn the event that there is demand for assets confiscation of bank customers by the court in a civil case , the bank must satisfy these requests without the need to break the bank secrecy provisions . So in a nutshell are as follows : Officers who conduct forfeiture of the deposit from customer deposits and the goods must surrender warrant ; foreclosures signed by the authorized officer concerned agencies ; confiscation for the benefit of a criminal case must submit a letter in addition to confiscation orders , officials are also concerned should mnyerahkan license from the Chairman of the local District Court , except in cases of very necessary and urgent it without a permit from the Chairman of the local Courts ; confiscation for the benefit of civil cases in addition must submit a warrant of seizure, officials are also concerned must submit a letter of Determination oppression Judge the local court ; When officials confiscate customer deposits with financial data customers want to know who confiscated , the official concerned must first obtain written permission from the Management of Bank Indonesia .